Contribution of a harpin protein from X anthomonas axonopodis pv. citri to pathogen virulence - Sgro, Germán Gustavo (2012)
Xanthomonas axonopodis pv. citri (Xac), the bacterium that causes citrus canker, contains a gene in the hrp [for hypersensitive response (HR) and pathogenicity] cluster that encodes a harpin protein called Hpa1. Hpa1 produced HR in the nonhost plants tobacco, pepper and Arabidopsis, whereas, in the host plant citrus, it elicited a weak defence response with no visible phenotype. Co-infiltrations of Xac with or without the recombinant Hpa1 protein in citrus leaves produced a larger number of cankers in the presence of the protein. To characterize the effect of Hpa1 during the disease, an XacDhpa1 mutant was constructed, and infiltration of this mutant caused a smaller number of cankers. In addition, the lack of Hpa1 hindered bacterial aggregation both in solution andpv. citri (Xac), the bacterium that causes citrus canker, contains a gene in the hrp [for hypersensitive response (HR) and pathogenicity] cluster that encodes a harpin protein called Hpa1. Hpa1 produced HR in the nonhost plants tobacco, pepper and Arabidopsis, whereas, in the host plant citrus, it elicited a weak defence response with no visible phenotype. Co-infiltrations of Xac with or without the recombinant Hpa1 protein in citrus leaves produced a larger number of cankers in the presence of the protein. To characterize the effect of Hpa1 during the disease, an XacDhpa1 mutant was constructed, and infiltration of this mutant caused a smaller number of cankers. In addition, the lack of Hpa1 hindered bacterial aggregation both in solution andhrp [for hypersensitive response (HR) and pathogenicity] cluster that encodes a harpin protein called Hpa1. Hpa1 produced HR in the nonhost plants tobacco, pepper and Arabidopsis, whereas, in the host plant citrus, it elicited a weak defence response with no visible phenotype. Co-infiltrations of Xac with or without the recombinant Hpa1 protein in citrus leaves produced a larger number of cankers in the presence of the protein. To characterize the effect of Hpa1 during the disease, an XacDhpa1 mutant was constructed, and infiltration of this mutant caused a smaller number of cankers. In addition, the lack of Hpa1 hindered bacterial aggregation both in solution andDhpa1 mutant was constructed, and infiltration of this mutant caused a smaller number of cankers. In addition, the lack of Hpa1 hindered bacterial aggregation both in solution and in planta. Analysis of citrus leaves infiltrated with Hpa1 revealed alterations in mesophyll morphology caused by the presence of cavitations and crystal idioblasts, suggesting the binding of the harpin to plant membranes and the elicitation of signalling cascades. Overall, these results suggest that, even though Hpa1 elicits the defence response in nonhost plants and, to a lesser extent, in host plants, its main roles in citrus canker are to alter leaf mesophyll structure and to aggregate bacterial cells, and thus increase virulence and pathogen fitness.We expressed the N-terminal and C-terminal regions and found that, although both regions elicited HR in nonhost plants, only the N-terminal region showed increased virulence and bacterial aggregation, supporting the role of this region of the protein as the main active domain.. Analysis of citrus leaves infiltrated with Hpa1 revealed alterations in mesophyll morphology caused by the presence of cavitations and crystal idioblasts, suggesting the binding of the harpin to plant membranes and the elicitation of signalling cascades. Overall, these results suggest that, even though Hpa1 elicits the defence response in nonhost plants and, to a lesser extent, in host plants, its main roles in citrus canker are to alter leaf mesophyll structure and to aggregate bacterial cells, and thus increase virulence and pathogen fitness.We expressed the N-terminal and C-terminal regions and found that, although both regions elicited HR in nonhost plants, only the N-terminal region showed increased virulence and bacterial aggregation, supporting the role of this region of the protein as the main active domain.